Centering and marginalization in introductory university physics classrooms - Scherr, Rachel E.; Hairston, W. Tali; McKagan, Sarah B.; Miller, Sophie (Frontiers in Education, 2023)
Introduction Research-based instructional strategies in physics promote active participation in collaborative activities as a primary means for students to construct understanding. Discussions of physics content are also negotiations of social relations. Methods Video analysis of small-group collaborative learning activities in introductory physics classrooms at three different universities, using situated learning theory analyses that include a critical consciousness lens. Results Students’ ability to actively participate in sensemaking may be limited by their peripheral or marginalized position. Some people seem to be centered (or marginalized) for reasons other than the strength of their physics reasoning, and some people’s contributions are elevated (or neglected) for reasons other than their scientific merit. Discussion Some of the behavioral patterns that we observe typify racialized and gendered interactions that are common in broader U.S. society.